DAMPAK PANDEMI COVID-19 TERHADAP PASAR MODAL INDONESIA (EVENT STUDY PADA PERUSAHAN PERBANKAN DI BURSA EFEK INDONESIA) (JEA17: Jurnal Ekonomi Akuntansi, 2022)
Covid-19 was first announced by the Indonesian government on March 2, 2020. This study will discuss the existence of abnormal differences in return, trading volume, and market capitalization before and after the announcement of Covid-19 in March 2020 at banking companies on the Indonesia Stock Exchange. The research data used is secondary data derived from banking companies listed on the Indonesia Stock Exchange. Sample selection is carried out by purposive sampling method where the data of banking companies is sampled by 12. The data analysis conducted in this study used the Independent Sample Test. The results of this study stated that there was no abnormal difference in return, trading volume, and market capitalization before and after the Covid-19 announcement in March 2020.